ANALISIS PENERIMAAN TEKNOLOGI PERPUSTAKAAN DIGITAL PADA PERPUSTAKAAN PERGURUAN TINGGI SWASTADI SUKOHARJO - Hestin Mutmainah, Andri Nurtantiono Heny Kurnianingsih (PARADIGMA, 2015)
The purpose of this study was to determine and analyze how influences Perceived Usefulness and Perceived Ease of Use to interest students in the College of Sukoharjo to use the digital library . This research try to apply or the Technology Acceptance Model ( TAM ) which describes the influence Perceived Usefulness and Perceived Ease of Use on the Acceptance of IT. With the instrument questionnaires , research conducted in three private universities in the region Sukoharjo ie Muhammadiyah University of Surakarta , Univet Bangun Nusantara and STIE Surakarta with student respondents Colleges in Sukoharjo with sample totaled 300 students with details per University of 100 people . Using multiple regression , F test and t test , this study finally obtain the following results 1 ) Perceived Easy of Use and Perceived Usefulness are jointly significant effect on the Acceptance use of Digital Libraries the University in Sukoharjo , 2 ) Perceived Ease of Use partially significant effect on the Acceptance use of Digital Libraries the University in Sukoharjo , and 3 ) Perceived usefulness at two universities, namely the Universitas Muhammadiyah Surakarta and Univet Bangun Nusantara Sukoharjo partially significant effect on the use of the Library Reception digital on University in Sukoharjo . While in STIE Surakarta Perceived Usefulness partially no significant effect on Admission use Digital Library. Keywords :Technology Acceptance Model, Perceived Usefulness, Perceived Ease of Use